Factors influencing customer’s satisfaction towards 5-star hotel services in Johor Bahru / Nurul Amanina Sulaiman - Sulaiman, Nurul Amanina (Faculty of Business and Management, 2019)
The purpose of this research is to study the factors influencing customer’s satisfaction towards 5-star hotel services in Johor Bahru. While service quality is considered as an important factor on generating customer satisfaction and repurchase intention.